Measuring the medication literacy level of community residents: a cross-sectional study - Huang, Lixing; Wei, Fenfang; Liu, Yangjun; Xu, Jialin; Wu, Jianru; Wang, Qian; Wang, Shuling; Wu, Wenyu (Frontiers in Public Health, 2025)
ObjectiveTo assess the current status and identify factors influencing the medication literacy level of community residents, providing a scientific basis to enhance medication literacy and effectively promote the safe use of medications.MethodsA questionnaire survey was conducted among 2,008 community residents in Shenzhen, employing economic stratification and proportionate sampling methods. The analysis utilized various statistical methodologies, including T-tests, F-tests, multiple linear stepwise regression, and structural equation modeling to assess the current medication literacy status and the factors influencing it.ResultsThe levels of medication literacy among community residents typically exhibit a normal distribution. Specifically, 10.16% of residents achieved the excellent level, 40.49% reached the good level, 37.40% were classified as passing, and 11.95% were deemed to have failed. The analysis of factors influencing medication literacy revealed that demographic characteristics, such as age and educational level, as well as various elements of medication knowledge, attitude, behaviors, and skills, significantly impact medication literacy. Notably, medication knowledge emerged as the most critical factor. Structural equation modeling demonstrated that medication knowledge, attitude, behaviors, and skills mediate medication literacy, which can indirectly affect medication literacy and be utilized in multiple ways to improve it and ensure the safety of medication use effectively.ConclusionThe level of medication literacy among community residents was commendable. However, the proportion of individuals with high medication literacy levels remained insufficient. Key influencing factors, such as medication knowledge, attitude, behaviors, and skills, are explored, offering insights for the government to implement initiatives that publicize medication knowledge, monitor and improve public medication behaviors, promote health education, and enhance community medication literacy and health development.